INFORMATION TECHNOLOGIES IN ECONOMIC EDUCATION (Journal of Information Technologies in Education (ITE), 2011)
In the article the basic aspects of the use of modern information technologies in an educational process are examined. Described directions of introduction of information technologies in economic education. Problems which are related to practice of professional preparation of specialists of economic specialities are examined. The role of information technologies in professional activity of specialists of economic type is underlined.
Keywords: highly skilled specialist; information educational technologies; informative systems; professional activity; professional preparation; program facilities informative-of communication; technologies